PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT DIAWALI POWERPOINT TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS XI SMAN 1 SOLOK SELATAN TAHUN PELAJARAN 2013/2014 - Nengsih, Fitra - (Pendidikan Biologi, 2014)
Based on the results of interview with one of the of biologyâs teachers of XI grade at SMAN 1 Solok Selatan, it was found that the students have difficulty to understand the material of reproduction system. It was proved from the results of the students average daily tests that is under KKM (Minimum Achievement Criteri ia) which is 70. Then, teacher at SMAN 1 Solok Selatan had never apply group learning in the form of a team competition and learning is centered on teacher. This research to find out the result of students learning in biology of XI grade at SMAN 1 Solok Selatan in academic year 2013/2014 with the implementation of active learning strategies learning tournament type begins with powerpoint. This research is an experimental study with Randomized Control-Group Postest Only Design. The population of the study are all of XI grade students of SMAN 1 Solok Selatan in academic year 2013/2014 consist of four class. Technique sampling is done by purposive sampling. XI A1 class as experiment class and XI A2 class as control class. The average results of the test for the experimental class students is 79.5 and 60.18 for the control class. Based on the results of hypothesis testing using t-test obtained t> t table is 6.35> 1.67. It can be concluded that the learning outcomes of biology students by applying active learning strategies learning tournament type begins with powerpoint is better than the learning outcomes of students by applying conventional learning.